SOCIALIZATION OF DETERMINING TYPES OF BUSINESS FOR VILLAGE-OWNED ENTERPRISES (BUMDES) IN ILEBOLI VILLAGE. - Masneno, Stefania; Banunaek, Ernestin Silvia; Molan, Kristianus Simon H.; Welin , Elisabeth D.M; Lamawuran, Yosef Dionisus; Lawalu, Stephanie Perdana Ayu (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service aims to increase the knowledge and experience of village governments and Village Consultative Bodies (BPD) about the establishment of Village-Owned Enterprises (BUMDES). BUMDES can become a village economic powerhouse by managing village potential and providing social and non-economic benefits. However, village governments and BPDs are still reluctant to establish BUMDES due to lack of knowledge and experience. This community service focuses on capacity building for village governments, BPDs, and community leaders to establish BUMDES and develop innovative programs. Thus, this activity can provide added value for increasing village original income and improving the welfare of village communities. Through the establishment of BUMDES, the role of middlemen who harm farmers can be controlled, and transaction costs can be reduced. This community service is expected to make a real contribution to strengthening village capacity.